2015
DOI: 10.1007/s00384-015-2332-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of autofluorescence imaging can accurately and objectively assess the severity of ulcerative colitis

Abstract: The quantified AFI is considered to be an accurate and objective indicator that can be used to assess the activity of ulcerative colitis, particularly for less-experienced endoscopists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
(31 reference statements)
0
18
0
Order By: Relevance
“…We also reported that the quantification of AFI was useful for assessing the severity of UC and that the intensity of AFI was inversely related to the histological severity. Furthermore, the quantified AFI showed a high level of accuracy and excellent inter-observer consistency [54].…”
Section: The Assessment Of Inflammation In Uc Patientsmentioning
confidence: 86%
“…We also reported that the quantification of AFI was useful for assessing the severity of UC and that the intensity of AFI was inversely related to the histological severity. Furthermore, the quantified AFI showed a high level of accuracy and excellent inter-observer consistency [54].…”
Section: The Assessment Of Inflammation In Uc Patientsmentioning
confidence: 86%
“…By adding an RGB (red, green, and blue) additive color model in silico, a strong inverse correlation between the green color component of AFI images and the severity of the mucosal inflammation was found [10]. In a similar prospective study by Moriichi et al, 135 WLE and AFI images from the same lesion in 43 patients with UC were evaluated by eleven endoscopists [11]. The AFI intensity significantly inversely correlated with the histologically graded severity of inflammation, and AFI was superior to standard white-light video endoscopy (SVE) regarding detection of inflammation (85% vs. 79%).…”
Section: Afi In Intestinal Inflammationmentioning
confidence: 99%
“…Both fluorescence and autofluorescence endoscopy are emerging imaging techniques that rely on visualization of fluorescence light (wavelength: 500–630 nm) emitted by either administered or endogenous fluorophores. In a prospective study of 43 patients with UC, the yield of autofluorescence imaging was superior to WLE in inflammation detection (85% versus 79%) [ 52 ]. Fluorescence endoscopy with 5-aminolevulinic acid (5-ALA) in comparison with WLE showed no significant difference in the dysplasia detection rate in IBD [ 53 ].…”
Section: Advanced Endoscopic Imaging Techniquesmentioning
confidence: 99%